Analysis of engine cylinder block with fins by varying different materials. (2023) - Subbiah, M.; Balamurugan, S.; Jayakumar, K.; Karthick, R.
Abstract: Aluminium alloy AA 6061 material is used in this study, and the engine cylinder is one of the most important automotive products that is subjected to high-temperature changes and thermal stresses. Fins are placed on the surface of the cylinder to boost the rate of heat transmission, which helps to cool the cylinder down more quickly. It is beneficial to perform thermal analysis on the engine cylinder fins to determine the amount of heat dissipation occurring inside the cylinder. Because increasing the surface area results in an increase in the heat dissipation rate, developing a large complex engine is extremely difficult. By altering the geometry of cylinder fins and analyzing the results with the Ansys workbench, the primary goal of this paper is to understand the thermal properties of cylinder fins. With the help of CREO parametric software, the geometries are transformed into a 3D model, which is then subjected to thermal analysis using the Ansys workbench. It is important to understand how temperature distribution changes over time since it is useful in many applications, such as cooling. The accurate thermal simulation may allow for the identification of important design parameters that will improve the life of the product. In the present work, the three different materials of AA6061, cast iron and AZ31 magnesium alloys were chosen during the simulation of temperature and heat flux distribution on the engine block and were analyzed. The aluminium alloy 6061 utilized in the fabrication of the cylinder fin body has a thermal conductivity of 160 – 170 W/mk which showed good performance and it is recommended in the construction of the cylinder fin body.